PERAN STRATEGIS KEMENTERIAN SOSIAL BAGI PENGUATAN PROGRAM BANTUAN PANGAN NON-TUNAI PASCA COVID-19 - Fatmawati, Fatmawati; Mulazid, Ade Sofyan (EMPATI: Jurnal Ilmu Kesejahteraan Sosial, 2024)
Abstract. This research aims to evaluate the implementation of the post-COVID-19 non-cash food assistance (BPNT) policy and analyze whether the distribution process carried out by the Ministry of Social Affairs is running according to procedures. Apart from that, the inhibiting and supporting factors for the BPNT distribution process were also analyzed. This research uses qualitative descriptive. Research informants consisted of bureaucrats, policy makers and beneficiary communities. The research results show that the government through the Ministry of Social Affairs has a strategic role in dealing with social problems, including the family hope program, financial support, direct financial support to village treasuries, social support to fulfil basic needs in the Jabodetabek area, pre-employment cards, basic food cards, and electricity subsidies. Policy implementers fail to comply with policy standards and objectives by intentionally violating procedures that benefit certain individuals for personal gain. The obstacles to this program are that policy implementation does not run smoothly, because several names of beneficiaries are not included in the Integrated Social Welfare Data (DTKS), incorrect redistribution of benefits, and inappropriate benefits and use of aid. funds are inaccurate. not used to buy necessities. This program is supported by strict monitoring and evaluation by the government so that it can minimize problems in the beneficiary communities. The theoretical implications of this research will contribute to the development of literature to examine the strategic role of the Ministry of Social Affairs and the implementation of the BPNT program to explain preventive and supportive factors after COVID-19. In practice, it can also provide consideration to the Ministry of Social Affairs, especially the Director General of Social Protection and Security when preparing a strategy for implementing the BPNT program.Keywords: Strategic Role, Food Assistance, Economic Recovery, COVID-19 Pandemic. Abstrak. Penelitian ini bertujuan untuk mengevaluasi implementasi kebijakan bantuan pangan non-tunai (BPNT) pasca COVID-19 dan menganalisis proses penyaluran yang dilakukan Kementerian Sosial apakah berjalan sesuai prosedur. Selain itu juga dianalisis faktor penghambat dan pendukung proses penyaluran BPNT. Penelitian ini, menggunakan deskriptif kualitatif. Informan penelitian ini terdiri dari birokrat, pengambil kebijakan, dan masyarakat penerima manfaat. Hasil penelitian menunjukkan bahwa pemerintah melalui Kementerian Sosial mempunyai peran strategis dalam menangani permasalahan sosial antara lain program keluarga harapan, dukungan dana, dukungan keuangan langsung ke kas desa, dukungan sosial pemenuhan kebutuhan dasar di wilayah Jabodetabek, kartu prakerja, kartu sembako, dan subsidi listrik. Pelaksana kebijakan gagal mematuhi standar dan tujuan kebijakan dengan sengaja melanggar prosedur yang menguntungkan individu tertentu demi keuntungan pribadi. Hambatan program ini adalah implementasi kebijakan tidak berjalan lancar, karena beberapa nama penerima manfaat tidak terdapat dalam Data Terpadu Kesejahteraan Sosial (DTKS), redistribusi manfaat yang tidak tepat, dan manfaat serta penggunaan bantuan yang tidak tepat. dana tidak akurat. tidak digunakan membeli kebutuhan pokok. Program tersebut didukung dengan monitoring dan evaluasi yang ketat oleh pemerintah sehingga dapat meminimalisir permasalahan masyarakat penerima manfaat. Implikasi penelitian ini secara teoritis akan memberikan kontribusi terhadap pengembangan literatur untuk mengkaji peran strategis Kementerian Sosial dan pelaksanaan program BPNT untuk menjelaskan faktor preventif dan supportif pasca COVID-19. Dalam praktiknya juga bisa memberikan pertimbangan kepada Kementerian Sosial, khususnya Dirjen Perlindungan dan Jaminan Sosial ketika menyiapkan strategi implementasi program BPNT.Kata Kunci: Peran Strategis, Bantuan Pangan, Pemulihan Ekonomi, Pandemi COVID-19.